Not predetermined: ‘Fusion-Image’ and Multicultural Art Education Based on Sino-US Portrait Painting Project Practice - Chen, Lei; Carter-Fisher, Miguel (The Canadian Art Teacher / Enseigner les arts au Canada)

(untitled) (Canadian Society for Education through Art / Société canadienne d’éducation par l’art, 2023)
Students from three universities in China and the United States worked together on a portrait painting project called ‘Fusion-Image’. It is meant to get youths trading photos of their peers who live on different continents to make art. In addition to portraiture's ability to shed light on the human, emotional, and spiritual, 'Fusion-Image' goes beyond this to pique and address students' interest in various materials and techniques, including digital painting. At the study's conclusion, many participants expressed gratitude for allowing them to question and trouble previously held biases. The project is a practical experiment on artistic creation that may spark respect and tolerance, it illuminates art education in the context of social responsibility for cultural diversity. This has ramifications for the development of art curricula, for we believe that an attitude free of stereotypes in the classroom will produce more engaging and versatile pedagogical and scholastic outputs. The purpose of this article is to examine how art education for students of different cultures, ethnicities, and regions can help confront cross-cultural issues and, on this basis, enhance thinking about core issues in art, such as tradition, ideas, spirituality, times, and many other matters, based on the work of two art teachers in China and the USA.